Visual Communication as a Characteristic of Information Society. - Melkonyan, Nvard; Karaperyan, Anna (Journal of Sociology: Bulletin of Yerevan University, 2018)
The cultural, social, economic and political transformations that took place in public life in the 21st century led to serious changes in the context of the processes of interaction. As a result, the forms and purposes of communication have also been changed. Today one of the most important goals of communication is the demonstration of own social status and self-presentation. In this situation arises the problem of visualization of public life through visual communication. The main goals of social networks’ users are self-presentation, socialization, and integration. This article focuses on the detection of trends of visualization in public life. As the best platforms for the implementation of visual communication, we have observed the social networks Facebook and Instagram. The changes, which may arise in connection with the increase of the visual component in social networks, as well as the growing number of users of social networks, indicate that the social life today is largely based on visual communication.